1991
DOI: 10.1128/jb.173.23.7416-7422.1991
|View full text |Cite
|
Sign up to set email alerts
|

The Staphylococcus aureus mec determinant comprises an unusual cluster of direct repeats and codes for a gene product similar to the Escherichia coli sn-glycerophosphoryl diester phosphodiesterase

Abstract: The DNA sequence located between mecA, the gene that codes for penicillin-binding protein PBP2', and insertion sequence-like element IS431mec has been termed hypervariable because of its length polymorphism among different staphylococcal isolates. We sequenced and characterized the hypervariable region of the methicillin resistance determinant (mec) isolated from Staphylococcus aureus BB270. Within the 2,040-bp hypervariable region, we identified an unusual accumulation of long direct repeats. Analysis of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
44
0
4

Year Published

2000
2000
2019
2019

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(48 citation statements)
references
References 42 publications
0
44
0
4
Order By: Relevance
“…4). This dru is responsible for the length polymorphism of SCCmec elements (34). There are four such dru's in strain TSGH 17 and three in strain WIS.…”
Section: Resultsmentioning
confidence: 99%
“…4). This dru is responsible for the length polymorphism of SCCmec elements (34). There are four such dru's in strain TSGH 17 and three in strain WIS.…”
Section: Resultsmentioning
confidence: 99%
“…The genomic DNA was digested with EcoRI and BglII restiction enzymes, and hybridized with two probes prepared from plasmid pBBB30 (233). HVR probe I is a 3.6-kb fragment that recognizes the HVR of the mec DNA, starting within the mecA gene and reaching up to IS431 mec.…”
Section: Hypervariable Region (Hvr) Hybridizationmentioning
confidence: 99%
“…An analysis of sporadic strains from the year 1995 revealed only three additional HVRtypes, each encountered in only one strain. Previous studies have shown that hypervariable region analysis by PCR and sequencing can be used to distinguish different mec DNA types (191,233,308). Five to eighteen different HVR-types have been identified in collections of 24-254 strains on the basis of differences in either the number or the sequence of dru repeats (185,191,242,246,308).…”
Section: Mec Hypervariable Regionmentioning
confidence: 99%
“…Für die mecA-Gen assoziierte DNS wurde dazu bisher die PCRAnalyse des mec-Regulons eingesetzt [3,4]. Im Berichtszeitraum wurde zusätz-lich der PCR-Nachweis der repetitiven dru-Sequenzen eingeführt, die Bestandteil der mecA-assoziierten DNS sind ( [5], Beispiel in Abb. 6).…”
Section: Weiterentwicklung Der Molekularen Typisierungunclassified